A study on acceptance of mobileschool at secondary schools in Malaysia: Urban vs rural - Hashim, A.S. (American Institute of Physics Inc., 2017)
Developing countries are in dilemma where sophisticated technologies are more advance as compared to the way their people think. In education, there have been many novel approaches and technologies were introduced. However, very minimal efforts were put to apply in our education. MobileSchool is a mobile learning (m-learning) management system, developed for administrative, teaching and learning processes at secondary schools in Malaysia. The paper presents the acceptance of MobileSchool between urban and rural secondary schools in Malaysia. Research framework was designed based on Technology Acceptance Model (TAM). The constructs of the framework include computer anxiety, self-efficacy, facilitating condition, technological complexity, perceived behavioral control, perceive ease of use, perceive usefulness, attitude and behavioral intention. Questionnaire was applied as research instrument which involved 373 students from four secondary schools (two schools in urban category and another two in rural category) in Perak. Inferential analyses using hypothesis and t-test, and descriptive analyses using mean and percentage were used to analyze the data. Results showed that there were no big difference (<20) of all acceptance constructs between urban and rural secondary schools except computer anxiety. © 2017 Author(s).